Geographic Information System Of Land Mapping Certification Of Rice Seeds In Bpsb, Subang Regency - Jaja Hasan Badriawan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the development of a geographic information system for mapping land certification for rice seeds at the Subang District's seed supervision and certification center based on (web gis). The geographic information system for mapping the land for certification of rice seeds at the BPSB (Seed Monitoring and Certification Agency) of Subang Regency is closely related to spatial data. The design or modeling of this system uses a modeling language, namely (Unified Modeling Language), and in its development using a method approach (Rational Unified Process) to determine the system structure's needs. Where the results of this analysis will be a system that will be developed, namely a geographic information system for mapping the land for certification of rice seeds at the Subang District's seed supervision and certification center is expected to simplify and improve performance at BPSB Subang Regency in managing land data so that it has more information value.